Promoting Gender Awareness Through Digital Storybook: A Case Study in Grade 10 Senior High School ELT - Firdhausya, Alina; Mustofa, Ali; Retnaningdiyah, Pratiwi (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2025)
This study investigates how digital storybooks can help high school English classes in the tenth grade become more gender aware. Few research have looked at how secondary school students react critically to gender narratives, despite the fact that many earlier studies have looked at gender bias in children's novels and textbooks. Eight students engaged with the digital storybook Too Young to Marry. Through focus groups, role-reversal exercises, and guided reading using a qualitative case study design. To find out how students felt about gender equality and representation, data were subjected to thematic analysis. The findings showed that pupils could recognize both gender stereotypes—like girls being coerced into child marriage—and counter-stereotypes—like male characters who defy patriarchal expectations. Students' opinions on equality, especially with regard to education as a right for both sexes, were impacted by reading and debating the storybook. Additionally, by encouraging empathy and critical thinking, the role-reversal exercises helped students question cultural norms and envision more just alternatives. According to the study's findings, digital storybooks can be an effective means of fostering literacy development, advancing gender equality in secondary education, and fusing language acquisition with social consciousness.